Correlations of carotenoid content and transcript abundances for fibrillin and carotenogenic enzymes in Capsicum annum fruit pericarp. (March 2015) - Kilcrease, James; Rodriguez-Uribe, Laura; Richins, Richard D.; Arcos, Juan Manuel Garcia; Victorino, Jesus; O'Connell, Mary A.
Graphical abstract: Highlights: Chromoplasts in Capsicum annuum pericarp have different shapes. β-Carotene, β-cryptoxanthin and total carotenoid are correlated. Negative correlation between violaxanthin and capsanthin in pericarp. Positive correlation between Fbn1 and CrtZ-2 transcripts in pericarp. Abstract: The fruits of Capsicum spp. are especially rich sites for carotenoid synthesis and accumulation, with cultivar-specific carotenoid accumulation profiles. Differences in chromoplast structure as well as carotenoid biosynthesis are correlated with distinct carotenoid accumulations and fruit color. In the present study, the inheritance of chromoplast shape, carotenoid accumulation profiles, and transcript levels of four genes were measured. Comparisons of these traits were conducted using fruit from contrasting variants, Costeño Amarillo versus Costeño Red, and from F1 hybrids; crosses between parental lines with novel versions of these traits. Intermediate chromoplast shapes were observed in the F1, but no association between specific carotenoid accumulation and chromoplast shape was detected. Increased total carotenoid content was associated with increased β-carotene and violaxanthin content. Transcript levels for phytoene synthase ( Psy ) and β-carotene hydroxylase ( CrtZ-2 ) were positively correlated with increased levels of specific carotenoids. No correlation was detected between transcript levels of capsanthin/capsorubin synthase ( Ccs ) and carotenoid composition or chromoplast shape. Transcript levels of fibrillin, were differentially correlated with specific carotenoids, negatively correlated with accumulation of capsanthin, and positively correlated with violaxanthin. The regulation of carotenoid accumulation in chromoplasts in Capsicum fruit continues to be a complex process with multiple steps for control.